2017
DOI: 10.2134/agronj2016.10.0566
|View full text |Cite
|
Sign up to set email alerts
|

Yield Gains in Extra‐Early Maize Cultivars of Three Breeding Eras under Multiple Environments

Abstract: Core Ideas The study determined genetic improvement in grain yield of the cultivars during the breeding eras, investigated trait associations, and identified high‐yielding and stable cultivars across multiple‐stress and non‐stress environments. The study revealed an annual genetic gain of 2.72 and 2.28% for the cultivars under multiple‐stress and non‐stress environments. Cultivars 2004 TZEE‐Y Pop STR C4, TZEE‐W Pop STR QPM C0, TZEE‐W Pop STR BC2 C0 of era 2 and TZEE‐W STR 107 BC1, TZEE‐W Pop STR C5, and 2012 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
11
27
1
Order By: Relevance
“…The extra-early cultivars showed an annual genetic gain of 3.28%, with a realized yield increase of 0.034 Mg ha −1 yr −1 under drought conditions, and 2.25% annual yield gain corresponding to an annual increase of 0.068 Mg ha −1 under rainfed conditions, which are greater than the yield gains obtained for the early-maturing cultivars reported by Badu-Apraku et al (2013a), who reported annual yield gains of 1.1 (0.014 Mg ha −1 ) and 1.3% (0.040 Mg ha −1 ) under drought and well-watered conditions, respectively. The annual yield gain obtained for this set of extra-early maize cultivars under drought was also higher than the annual yield gains of 2.56% reported under artificial Striga infestation (Badu-Apraku et al, 2016), 2.14% under low soil N (Badu-Apraku et al, 2017a, and 2.72% under multiplestress environments (Badu-Apraku et al, 2017b) for the same set of extra-early cultivars. Furthermore, the annual yield gain of 0.034 Mg ha −1 achieved under drought in the present study was greater than the gain of 0.029 Mg ha −1 obtained for CIMMYT's ESA early-maturing OPVs (Masuka et al, 2017b) and was comparable with the annual yield gain of 0.042 Mg ha −1 reported for the CIMMYT's ESA intermediate-late OPVs under random drought stress.…”
Section: Discussioncontrasting
confidence: 48%
“…The extra-early cultivars showed an annual genetic gain of 3.28%, with a realized yield increase of 0.034 Mg ha −1 yr −1 under drought conditions, and 2.25% annual yield gain corresponding to an annual increase of 0.068 Mg ha −1 under rainfed conditions, which are greater than the yield gains obtained for the early-maturing cultivars reported by Badu-Apraku et al (2013a), who reported annual yield gains of 1.1 (0.014 Mg ha −1 ) and 1.3% (0.040 Mg ha −1 ) under drought and well-watered conditions, respectively. The annual yield gain obtained for this set of extra-early maize cultivars under drought was also higher than the annual yield gains of 2.56% reported under artificial Striga infestation (Badu-Apraku et al, 2016), 2.14% under low soil N (Badu-Apraku et al, 2017a, and 2.72% under multiplestress environments (Badu-Apraku et al, 2017b) for the same set of extra-early cultivars. Furthermore, the annual yield gain of 0.034 Mg ha −1 achieved under drought in the present study was greater than the gain of 0.029 Mg ha −1 obtained for CIMMYT's ESA early-maturing OPVs (Masuka et al, 2017b) and was comparable with the annual yield gain of 0.042 Mg ha −1 reported for the CIMMYT's ESA intermediate-late OPVs under random drought stress.…”
Section: Discussioncontrasting
confidence: 48%
“…The agronomic and management practices adopted for the experiments have been reported by Badu-Apraku et al . 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Low N (30 kg/ha) experiments were carried out at Mokwa during the rainy seasons of 2015 and 2016 and Ile-Ife during the 2015 rainy season (Supplementary Table 2). Details on how the low soil N environment was achieved at Mokwa and Ile-Ife and the management practices observed have been described by Badu-Apraku 50 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted into farmers planting available seed that often has low vigor, which in turn affects the yield (Nkang and Umoh, 1997). It has been proved that cultivars respond differently to environment situations due to their genetic variability (Flajšman et al, 2019;Badu-Apraku et al, 2017). Hence researchers have explored the use genetic variability among germplasms to solve genetic and agronomic problems.…”
Section: Introductionmentioning
confidence: 99%